Why government effectiveness makes or breaks the cooperative movement - Andrew, Leviana; Shariffuddin, Norashikin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Cooperatives are member-driven organizations focused on shared goals and community upliftment rather than profit. Their success often depends on effective government support, as policies and regulations play a crucial role in enabling or hindering their growth.